INDUKSI KALUS DAN ORGANOGENESIS KULTUR IN VITRO Dendrobium lineale Rolfe - Djadja Siti Hazar Hoesen; Witjaksono Witjaksono; LA Sukamto (BERITA BIOLOGI, 2008)
Callus induction and organogenesis were evaluated in the protocorm like bodies (PLB) culture of Dendrobium lineale Rolfe (Orchidaceae). The globular PLB were cultured in Murashige and Skoog (MS) medium with half strength macronutrients QA MS), supplemented with thidiazuron (TDZ 0,1, 0,5 and 1) mg/1 and 2,4 Dichlorophenoxy acetic acid (2,4-D 0.1, 0.5, 1 and 5) mg/1 as treatments. The media containing 1 mg/1 TDZ and (1 and 5) mg/1 2,4-D was the best treatment for callus initiation (100%). The largest diameter of callus was obtained from 1 mg/1 TDZ (average 3.5 cm). Shoot buds regeneration achieved on 1 mg/1 TDZ (average 41.66 %). However roots regeneration was very low (average 6.66 %) obtained from 1 mg/1 2,4-D. The number of adventitious buds produced from the regenerated shoots on media without plant growth regulator